2021
DOI: 10.17583/ijep.7307
|View full text |Cite
|
Sign up to set email alerts
|

Does Use of Books and Electronic Media Associate to Joint Attention Skills and Temperament during the First Year of Life?

Abstract: Several researchers have found that media exposure through books or electronic media contribute to preschoolers’ development. However, research with behavioral measures and during the first years of life have not been carried out in Latin American contexts. The aim of the following research was to evaluate the relations between media exposure through electronic media and books with joint attention skills and temperament (i.e., effortful control, surgency and negative affect) during the first year of life. A fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 51 publications
0
3
0
1
Order By: Relevance
“…To this day, little is known about the relations between HLE, screen media exposure and infants' linguistic development in Latin America. Besides, most studies focus on TV and do not consider other technological devices (Gago Galvagno et al, 2021). Taking this into account, we examined the associations between the use of different electronic devices, HLE and children's early vocabulary size and use of sentences in a previous study.…”
Section: Introductionmentioning
confidence: 99%
“…To this day, little is known about the relations between HLE, screen media exposure and infants' linguistic development in Latin America. Besides, most studies focus on TV and do not consider other technological devices (Gago Galvagno et al, 2021). Taking this into account, we examined the associations between the use of different electronic devices, HLE and children's early vocabulary size and use of sentences in a previous study.…”
Section: Introductionmentioning
confidence: 99%
“…Es por entonces que, la realización de una práctica deportiva puede guardar relación con el En función de la antigüedad, aquellos que realizaban dichas actividades hace mayor tiempo, reportaron presentar mayor Autoconcepto físico que aquellos que lo realizaban con menor antigüedad. El uso de dispositivos surge como cuestión alarmante ya que en estos últimos años la comunicación digital incrementó de manera notoria mientras que, la comunicación presencial se ve disminuida (Gago Galvagno et al, 2021). En base a lo que sostienen Antolínez Merchán et al ( 2011) acerca de los efectos tanto positivos como negativos de su uso, presentaron cuatro problemáticas.…”
Section: Discussionunclassified
“…In fact, there are several studies that fail to show a relationship between media usage and cognitive milestones and language development. For example, Gago Galvagno et al ( 2021 ) found that in free play sessions with infants aged 9 to 13 months, there was no relationship between infant nonverbal behavior and different types of screens (though the use of books at home was associated with a greater number of nonverbal behaviors). Examining this relationship further, Tabullo and Gago-Galvagno ( 2022 ) found that with infants from 12 to 40 months, for children with a greater the number of books in the home, the shared use of a PCs together with the influx of reading by the family related to a greater amount of vocabulary and use of sentences, without obtaining significant relationships with the rest of the devices after controlling for sociodemographic variables (e.g., SES).…”
Section: Introductionmentioning
confidence: 99%
“…In this sense, digital media has become ubiquitous in families' daily routines (Madigan et al, 2020;Sas & Estrada, 2021), with digital content becoming more frequent and immersed in everyday life (Sas & Estrada, 2021;Simaes et al, 2022;Teichert, 2017). Given the widespread presence of digital media, it may come as no surprise that it has been identified as an influential factor not only in the education of children, but also in their development (Navarro et al, 2017;Gago Galvagno et al, 2021;Medawar et al, 2023). This is especially important to consider during the first few years of life, when children are showing rapid development in foundational abilities like language and motor skills (Bruner, 1975(Bruner, , 1982.…”
Section: Introductionmentioning
confidence: 99%